Life of Women in South Sulawesi during the Kahar Muzakkar Rebellion, 1953-1965 - Azizah, Nurul (JUSPI (Jurnal Sejarah Peradaban Islam), 2024)
This research examines the life of women in South Sulawesi when it is a study of the Kahar Mudzakkar rebellion in South Sulawesi, 1953-1965. The rebellion was carried out as a form of protest because there was no appreciation for the guerrillas in the Army after the war for independence took place. The form of this rebellious movement changed in 1953, when Kahar officially joined DI/TII in West Java. The merger of this movement with DI/TII has an impact on society. They began to seek the sympathy of the people and the clergy, drew boundaries between their territory and the Republic of Indonesia, and imposed Islamic law. This rebellion influenced women as vulnerable subjects. The androcentrism, patriarchy, and sexist interpretation of social and religious phenomena by the rebel movement Kahar Mudzakkar has led to gender inequality among women. This gender injustice occurs not only to those who live in areas controlled by the rebels, but also to those who live outside these areas. As a result, during the rebellion, women experienced subordination and violence.